Variations in enzyme activity of tebuconazole tolerant biotypes of Trichoderma viride - J.P. GUPTA, A. KUMAR* and (Indian Phytopathology, 2002)
Biotypes of T. viride (a mungbean rhizosphere isolate antagonistic to Macrophomina phaseolina; sensitive to 20ppm tebuconazole) tolerant to tebuconazole were obtained using UV or gamma-rays. The biotypes, UMT1A & UMT4 (tolerant to 50 ppm tebuconazole) and UMT1 & GMT2 (tolerant to 100 ppm tebuconazole) showed wide variations in morphological, physiological and biochemical traits. Among the biochemical characters, the ability to produce hydrolytic enzymes such as beta-1,4-endoglucanase, beta-1,3-glucanase and chitinase is of significance as they are implicated in the biological control of M. phaseolina. The enzyme activity was assayed in 10-day-old culture filtrate of T. viride using standard protocols. Except GMT2, all other biotypes expressed beta-1,4-endoglucanase activity, however, none of the biotypes produced significantly higher beta-1,4-endoglucanase activity than the wild type. The biotypes also showed variations in the expression of beta-1,3-glucanase and chitinase activity.